ISM PROPERTIES OF A MASSIVE DUSTY STAR-FORMING GALAXY DISCOVERED AT Z ∼ 7 - Strandet, M. L.; Weiß, A.; De Breuck, C.; Marrone, D. P.; Vieira, J. D.; Aravena, M.; Ashby, M. L. N.; Bethermin, M.; Bothwell, M. S.; Bradford, C. M.; Carlstrom, J. E.; Chapman, S. C.; et al. (The Astrophysical Journal, 2017)
Accepted by ApJL, Fixed compilation problem in v.2 International audience We report the discovery and constrain the physical conditions of the interstellar medium of the highest-redshift millimeter-selected dusty star-forming galaxy (DSFG) to date, SPT-S J031132−5823.4 (hereafter SPT0311−58), at z = 6.900 ± 0.002. SPT0311−58 was discovered via its 1.4 mm thermal dust continuum emission in the South Pole Telescope (SPT)-SZ survey. The spectroscopic redshift was determined through an ALMA 3 mm frequency scan that detected CO(6–5), CO(7–6) and [C I](2–1), and subsequently confirmed by detections of CO(3–2) with ATCA and [C II] with APEX. We constrain the properties of the ISM in SPT0311−58 with a radiative transfer analysis of the dust continuum photometry and the CO and [C I] line emission. This allows us to determine the gas content without ad hoc assumptions about gas mass scaling factors. SPT0311−58 is extremely massive, with an intrinsic gas mass of M gas = 3.3 ± 1.9 × 10 11 M. Its large mass and intense star formation is very rare for a source well into the Epoch of Reionization.